Shifting Patterns of Economic Growth and Rethinking Development - Lin, Justin Yifu; Rosenblatt, David (Taylor and Francis, 2013)
This paper provides an historical overview of both the evolution of the economic performance of the developing world and the evolution of economic thought on development policy. The twentieth century was broadly characterized by divergence between high-income countries and the developing world, with only a limited number (less than 10% of the economies in the world) managing to progress out of lower or middle-income status to high-income status. The last decade witnessed a sharp reversal from a pattern of divergence to convergence – particularly for a set of large middle-income countries. The latter phenomenon was also driven by increasing economic ties among developing countries and, on the intellectual scale, increased knowledge generation and sharing among the developing countries. Re-thinking development policy implies confronting these realities: twentieth century economic divergence, the experience of the handful of success stories, and the recent rise of the multi-polar growth world. This paper provides descriptive data and a literature survey to document these trends.